In Vitro and In Vivo Antimelanogenesis Effects of Leaf Essential Oil from Agathis dammara - Ho, Yu-Tung; Liu, I-Hsuan; Chang, Shang-Tzen; Wang, Sheng-Yang; Chang, Hui-Ting (Pharmaceutics, 2023)
Agathis species are widely distributed around Southeast Asia, Australasia, South Pacific islands, and etc. Traditionally, Agathis species have been used as the folk medicines, the common ethnopharmacological uses of Agathis genus are the treatments of headache and myalgia. This study aims to investigate the chemical composition of Agathis dammara (Lamb.) Rich. leaf essential oil and to explore its antimelanogenesis effect. The chemical constituents of leaf essential oil are analyzed using gas chromatography-mass spectrometry (GC-MS), the major constituents of leaf essential oil are sesquiterpenoids. The major constituents are δ-cadinene (16.12%), followed by γ-gurjunene (15.57%), 16-kaurene (12.43%), β-caryophyllene (8.58%), germacrene D (8.53%), and γ-cadinene (5.33%). As for the in vitro antityrosinase activity, leaf essential oil inhibit the tyrosinase activity of mushroom when the substrate is 3,4-dihydroxyphenylalanine (L-DOPA). Leaf essential oil prevents tyrosinase from acting as diphenolase and catalyzing L-DOPA to dopaquinone, and converting into dark melanin pigments. A. dammara leaf essential oil also exhibits the in vivo antimelanogenesis effect, leaf essential oil reduces 43.48% of melanin formation in zebrafish embryos at the concentration of 50 μg/mL. Results reveal A. dammara leaf essential oil has the potential for developing the skin whitening drug and depigmentation ingredient for hyperpigmentary disorders.